Tehničko opsluživanje drumskih tranportnih kapaciteta - Jašarević, Faruk; Dedić, Ismet (Promet - Traffic&Transportation, 2012)
The authors review transit volumes foreign tourists and their vehicles and in this concern refer to the deficiencies in the process of repair and servicing of foreign vehicles. With reference to the requirement and need of urgent repairs the authors recommend respective locations and systems of service management for these purposes. The existing structure and operation modes of the capacities is unsatisfactory, so that there is absolutely the need for the reconstruction and extension of the existing and building of new servicing capacities on locations with busy traffic to contribute to a better promotion of our country on the tourist trade community.